Analisis Penerapan Model Rancangan Struktur Metode Student Centre Learning (Scl) Dalam Mata Kuliah Sistem Akuntansi Dengan Kurikulum Berbasis Kompetensi (KBK) - Zahara; Afni, Zalida (Akuntansi dan Manajemen, 2016)
This research porpuse to design the structure of Student Centre Learning (SCL) methode in accounting system subject that use curriculum based on competency. This is an action research in accounting system study at accounting departement of Padang State Polytechnic. This research uses Kemmis dan Mac Tanggart model which is devided in 5 steps that are: 1. Planning, 2. Action&Observation, 3. Reflecting&Replanning, 4. Action&Observation and 5. Reflecting. The application of SCL metode in accounting system study will be evaluated based on the score of student respons and student academic score in accounting system. The student respons questioners are measured by Linkert scale. Datas of student respons and student academic score are classified for 5 level such as: 5=A=Very Good, 4=B=Good, 3=C=Fair, 2=D=Bad, and 1=E=Very Bad. All of score data will be analysed to define the appropriateness of SCL methode for accounting system subject. This research evalued the applicatian of 5 (five) SCL model that chosen as the result of the first step research (planning) i.e. Small Group Discussion, Discovery Learning, Role Play, Contextual Instruction dan Problem Based Learning. The result shown all the SCL method that is used in this research are â€œgoodâ€ for accounting system subject, based on student respons as â€œgoodâ€ as their academic score.